3D Stereolithography of Polymer Composites Reinforced with Orientated Nanoclay. (2017) - Eng, H.; Maleksaeedi, S.; Yu, S.; Choong, Y.Y.C.; Wiria, F.E.; Tan, C.L.C.; Su, P.C.; Wei, J.
Abstract: Polymer parts fabricated by 3D stereolithography (SL) tend to have much lower mechanical properties compared to their counterparts fabricated by conventional methods. Furthermore, due to cross linkage among polymer chains in the thermoset polymers, the SL printed parts tend to have low elongation and experience brittle fracture during failure. Various types of fillers have been added into photopolymer to improve the mechanical properties, with most of them being randomly dispersed. In this study, montmorillonite nanoclays (plate-shaped) are first exfoliated and homogenously dispersed in the photopolymer via several mixing steps, including sonification. After which, using the photopolymer dispersed with nanoclays in a bottom-up SL, the descending of build platform into the resin tank during the printing process provides a downward force to orientate the plate-shaped nanoclays in each layer. The nanoclays will be immobilized during photopolymerization upon ultra-violent (UV) exposure, thus maintaining their orientation and alignment. This process drastically improves the elongation by more than 100% and enhances the tensile stress and Young's Modulus in the X-Y plane. This paper will also discuss the dispersion, alignment, size and loadings of the montorillonite nanoclays. This new approach will open up possibilities of printing high performance parts using stereolithography, increasing its functionality.